Recombinant COL6 α2 as a Self-Organization Factor That Triggers Orderly Nerve Regeneration Without Guidance Cues - Fang, Zhou; Zou, Jian-Long (Frontiers in Cellular Neuroscience, 2021)
Collagen VI (COL6) in the microenvironment was recently identified as an extracellular signal that bears the function of promoting orderly axon bundle formation. However, the large molecular weight of COL6 (≈2000 kDa) limits its production and clinical application. It remains unclear whether the smaller subunit α chains of COL6 can exert axon bundling and ordering effects independently. Herein, based on a dorsal root ganglion ex vivo model, the contributions of three main COL6 α chains on orderly nerve bundle formation were analyzed, and COL6 α2 showed the largest contribution weight. A recombinant COL6 α2 chain was produced and demonstrated to promote the formation of orderly axon bundles through the NCAM1-mediated pathway. The addition of COL6 α2 in conventional hydrogel triggered orderly nerve regeneration in a rat sciatic nerve defect model. Immunogenicity assessment showed weaker immunogenicity of COL6 α2 compared to that of the COL6 complex. These findings suggest that recombinant COL6 α2 is a promising material for orderly nerve regeneration.